Pengaruh Model Pembelajaran Savi dan Tingkat Kepercayaan Diri terhadap Prestasi Belajar Siswa - Reni Nuraeni; Rahmat Permana; M. Fahmi Nugraha (Universitas Muhammadiyah Bangka Belitung, 2020)
This study was conducted to determine the effect of the SAVI (Somatic, Auditory, Visual, and Intellectual) learning model on the science learning achievement of fourth-grade students. student of SDN 1 Setiamulya District Tamansari. This type of research is the same experiment with a research design using Factorial Experimental design. The population in this research is grade IV SDN 1 Setiamulya District of Tamansari. The sample of this research is all grade IV SDN 1 Setiamulya amounting to 41 students. Data collection techniques are conducted with pretest and posttest test dan data analyzed using SPSS version 21. Data obtained are analyzed using descriptive statistics and inferential statistics. Based on the result of data analysis, obtained significance of 0,793 < 0,05, it can be concluded that Ho in reject and H1 is acceptable. This means that students’ confidence can influence the SAVI (Somatic, Auditory, Visual and Intellectual) model towards students’ learning performance in the Grade IV SDN 1 Setiamulya.